2021
DOI: 10.1371/journal.pone.0254021
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cut-off value for detecting colorectal cancer with fecal immunochemical tests according to age and sex

Abstract: In the fecal immunological test, a suitable cut-off value may be selected to classify results as either positive or negative. Our aim is to estimate the optimal cut-off value for detecting colorectal cancer in different age and sex groups. This is a multicentric retrospective cohort study of participants in CRC screening programs with FIT between 2006 and 2012. A total of 545,505 participations were analyzed. Cancers diagnosed outside of the program were identified after a negative test result (IC_test) up unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Our results suggest that 15 µg Hg/g should be the lowest FIT cut-off that a CRC screening programme should aim for, regardless of the patient’s gender and age. This recommendation is supported by a recent study by Vanaclocha-Espi et al which found the optimal FIT cut-off of around 15 µg Hg/g for the subgroup of women aged 60–69, which had the lowest FIT sensitivity among the subgroups evaluated (women and men, aged 50–59 and 60–69) [ 51 ].…”
Section: Discussionmentioning
confidence: 66%
“…Our results suggest that 15 µg Hg/g should be the lowest FIT cut-off that a CRC screening programme should aim for, regardless of the patient’s gender and age. This recommendation is supported by a recent study by Vanaclocha-Espi et al which found the optimal FIT cut-off of around 15 µg Hg/g for the subgroup of women aged 60–69, which had the lowest FIT sensitivity among the subgroups evaluated (women and men, aged 50–59 and 60–69) [ 51 ].…”
Section: Discussionmentioning
confidence: 66%
“…When this type of FOBT is used in screening, a cut-off point is applied to determine whether a result is positive or negative. It has also been demonstrated that the established cut-off point affects the IC rate, as can be seen in a previous study that observed how different FIT cut-off points lead to changes in the IC rate [11]. Other variables such as sex and age have been linked to the occurrence of IC, with studies showing that IC is more frequent in men and older populations [12,13].…”
Section: Introductionmentioning
confidence: 64%
“…The cut-off point for the FIT was 20 µg/g and a colonoscopy was offered as a confirmatory diagnostic test. The characteristics of these programmes and the outcomes associated with this cohort can be found in previous studies by Vanaclocha-Espí et al, 2021 and 2019 [11,17].…”
Section: Cribea-cin Projectmentioning
confidence: 77%
“…Several factors should be considered, such as systematic false-positive FIT results, costs, and the capacity of FIT laboratories and colonoscopy centers. Moreover, if iPCCRC risk is to be considered in relation to FIT IC risk, the chosen FIT positivity cutoff should be taken into account, as it is a determinant of FIT IC risk 37 .…”
Section: Discussionmentioning
confidence: 99%